Entrepreneurship Education and Green Economy Literacy as Determinants of Sustainable Entrepreneurial Intention: The Mediating Role of Self-Efficacy - Sutrisno; Ausat, Abu Muna Almaududi; Pramono, Susatyo Adhi; Syamsuri; Suherlan; Shafiq, Muhammad Aqib (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the effects of entrepreneurship education and green economy literacy on sustainable entrepreneurial intention, with self-efficacy as a mediating variable. A quantitative approach was employed using purposive sampling involving 128 university students in Jakarta who had completed or were enrolled in entrepreneurship courses. Data were collected using multi-item instruments adapted from previous entrepreneurship and sustainability studies and measured on a five-point Likert scale. Measurement adequacy was established through outer loadings ≥0.70, AVE ≥0.50, Cronbach’s Alpha and Composite Reliability ≥0.70, and the Fornell–Larcker criterion. Data were analyzed using SEM-PLS with 5,000 bootstrap resamples. The results show that entrepreneurship education (β = 0.381) and green economy literacy (β = 0.426) significantly enhance self-efficacy, while self-efficacy significantly increases sustainable entrepreneurial intention (β = 0.548). Self-efficacy significantly mediates the relationships between entrepreneurship education, green economy literacy, and sustainable entrepreneurial intention (β = 0.222, p < 0.001). Universities should embed green literacy into entrepreneurship curricula through sustainability case studies, green business projects, and incubation and mentoring activities designed to provide practical mastery experiences and strengthen students’ self-efficacy for sustainable entrepreneurship.